Defect Engineering of Oxygen‐Deficient Manganese Oxide to Achieve High‐Performing Aqueous Zinc Ion Battery. Issue 14 (14th February 2019) - Xiong, Ting; Yu, Zhi Gen; Wu, Haijun; Du, Yonghua; Xie, Qidong; Chen, Jingsheng; Zhang, Yong‐Wei; Pennycook, Stephen John; Lee, Wee Siang Vincent; Xue, Junmin
Abstract: A major limitation of MnO2 in aqueous Zn/MnO2 ion battery applications is the poor utilization of its electrochemical active surface area. Herein, it is shown that by generating oxygen vacancies ( V O ) in the MnO2 lattice, Gibbs free energy of Zn 2+ adsorption in the vicinity of V O can be reduced to thermoneutral value (≈0.05 eV). This suggests that Zn 2+ adsorption/desorption process on oxygen‐deficient MnO2 is more reversible as compared to pristine MnO2 . In addition, because of the fact that fewer electrons are needed for ZnO bonding in oxygen‐deficient MnO2, more valence electrons can be contributed into the delocalized electron cloud of the material, which aids in enhancing the attainable capacity. As a result, the stable Zn/oxygen‐deficient MnO2 battery is able to deliver one of the highest capacities of 345 mAh g −1 reported for a birnessite MnO2 system. This excellent electrochemical performance suggests that generating oxygen vacancies in MnO2 may aid in the future development of advanced cathodes for aqueous Zn ion batteries. Abstract : A major limitation of MnO2 in aqueous Zn/MnO2 ion battery applications is the poor utilization of its electrochemical active surface area. Herein, the superiority of Zn ion batteries engineered with oxygen vacancy in MnO2 framework is proposed and demonstrated. More accessible electrochemical active surface area and more electrons are available for electrochemical process, which aids in enhancing the attainable capacity.